First order autoregressive representation of Markov bi-dimensional chains of 1-order (Sciences & Technology. A, exactes sciences, 2006)
This paper suggests an extension of Lai’s results about the first order autoregressiverepresentation of Markov bi-dimensional chain of 1-order. In the case of markov chain withindependent components, we find of course the conditions validating these results for eachcomponent.